COMPARISON PRODUCTION BIOETHANOL FROM CELLULOSE USING BATCH DISTILLATION AND FLASH DISTILLATION PROCESS (GEOMATE Journal, 2018)
The process of distillation in either a batch distillation or flash distillation each have positionsand disadvantages, and the areas of batch distillation that have high columns can be synchronized with somethe stage more than one phases, and flash distillation have tall columns that matched equally to one step. Theadvantages of flash distillation have a shorter distillation time versus batch distillation, distillation bioethanolyield on flash batch distillation more than it is. This research aims to get purer bioethanol, more amount ofbioethanol as well as shorter time. Bamboo contains cellulose and high glucose, reduce the amount of ligninand pentose with pretreatment and lignification process, filtrate glucose produced in the fermentation usingenzymes. From the process of fermentation obtained bioethanol with 15%, then conducted the process ofdistillation, with variable timing and temperature. Bioethanol achieved with the levels of approximately 95%,of the process of batch distillation bioethanol yield obtained is smaller, longer time and higher levels of theflash distillation process, obtained yield bioethanol larger, shorter time and the lower levels.